2011
DOI: 10.1186/1756-6614-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Validity of multiplex biomarker model of 6 genes for the differential diagnosis of thyroid nodules

Abstract: BackgroundCurrently the cytological examination of fine needle aspiration (FNA) biopsies is the standard technique for the pre-operative differential diagnosis of thyroid nodules. However, the results may be non-informative in ~20% of cases due to an inadequate sampling and the lack of highly specific, measurable cytological criteria, therefore ancillary biomarkers that could aid in these cases are clearly needed. The aim of our study was to evaluate the mRNA expression levels of 8 candidate marker genes as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…DPP4 (CD26) encodes a membrane‐bound serine protease, a member of the dipeptidyl prolyl peptidase (DPP) family . Our findings are supported by literature reports that this gene significant increases in differentiated carcinomas vs. normal or benign thyroid nodules at average 46.19 times . In addition, some studies showed that DPP4 was downregulated in ATC with unclear mechanism, which was consistent with the expression level of our ACT specimen by QPCR.…”
Section: Discussionsupporting
confidence: 90%
“…DPP4 (CD26) encodes a membrane‐bound serine protease, a member of the dipeptidyl prolyl peptidase (DPP) family . Our findings are supported by literature reports that this gene significant increases in differentiated carcinomas vs. normal or benign thyroid nodules at average 46.19 times . In addition, some studies showed that DPP4 was downregulated in ATC with unclear mechanism, which was consistent with the expression level of our ACT specimen by QPCR.…”
Section: Discussionsupporting
confidence: 90%
“…Several other studies have supported an association between urinary glycine or PAG levels and status of oxidative stress [47,48,49,50,51,52] or inflammatory stress [52]. Finally, the predictive accuracy of this two-metabolite set was further validated with the LOOCV procedure, because the ROC curve may lead to an overestimation of the AUC if it is constructed using all samples [53]. The LOOCV procedure has an advantage of reducing the likelihood of developing an overly optimistic predictive model given the relatively small sample in our study [54].…”
Section: Discussionmentioning
confidence: 99%
“…In the follow-up studies, many researchers at other institutes confirmed the utility of TFF3 mRNA in diagnosing follicular carcinoma [10][11][12][13][14][15][16][17]. A more intriguing property of TFF3 mRNA is that papillary and anaplastic thyroid carcinomas also show low T/G ratios [9,18].…”
Section: Real-time Quantitative Polymerase Chain Reactionmentioning
confidence: 97%
“…However, in the case of TFF3 mRNA, the precise measurement of its expression levels in thyroid tumor cells in aspirates was difficult because it is interfered with peripheral blood cells or infiltrating lymphocytes that are aspirated simultaneously by FNAB. In fact, there has been only a few reports measuring TFF3 mRNA using thyroid aspirates [13][14][15][16]. Thus, selection of thyroid tumor cells in aspirated samples is crucial for the precise measurement of the T/G ratio in aspirates.…”
Section: Real-time Quantitative Polymerase Chain Reactionmentioning
confidence: 99%